2012
DOI: 10.1016/j.schres.2011.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Is it possible to have impaired neurocognition but good social cognition in schizophrenia?

Abstract: Social cognitive impairment in schizophrenia is common and associated with poor functional outcome. While correlations in the moderate range suggest that social cognition and neurocognition are separate but overlapping domains, less is known about whether intact neurocognition represents a “necessary but not sufficient” condition for intact social cognition, as has been suggested. In the present study we examined the following in a sample of 119 psychiatrically stable outpatients with schizophrenia: 1) correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 24 publications
5
50
0
3
Order By: Relevance
“…These impairments, which involve difficulties acquiring and processing general information, have profound effects on functioning throughout the course of the disorder [1][2][3][4]. Social cognition is also related to patient functioning and is of prime interest as a potential treatment target to improve functioning [5][6][7][8][9]. Social cognition ''includes specific mental operations underlying social interaction'' [4], and deficits in social cognition involve a ''compromised ability to infer and interpret others' feelings and a tendency to excessively ascribe negative emotions to others'' [10].…”
Section: Introductionmentioning
confidence: 99%
“…These impairments, which involve difficulties acquiring and processing general information, have profound effects on functioning throughout the course of the disorder [1][2][3][4]. Social cognition is also related to patient functioning and is of prime interest as a potential treatment target to improve functioning [5][6][7][8][9]. Social cognition ''includes specific mental operations underlying social interaction'' [4], and deficits in social cognition involve a ''compromised ability to infer and interpret others' feelings and a tendency to excessively ascribe negative emotions to others'' [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, this indicates that each ability only accounts for approximately 5% to 15% of the variance in the other constructs. Moreover, a number of studies have examined whether these processes can be disentangled from one another, with a growing consensus suggesting that neurocognition, social cognition, and metacognition are related, but independent constructs (Pinkham et al, 2003;Allen et al, 2007;Fanning et al, 2012;Lysaker et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a large portion of improvement of social cognition (83%) is explained by enhancement of neuropsychological performance (Vauth et al, 2004). These findings indicate that enhancing neuropsychological performance is essential for ameliorating social cognition (Fanning et al, 2012), and, consequently, for restoring functional outcome.…”
Section: Intervening Variables and Social Cognition: The Relations Tomentioning
confidence: 79%
“…Rather, social cognition may be enhanced by the recovery of neurocognitive performance in that case. In fact, a recent study (Fanning et al, 2012) has reported that the percentage of patients with impaired neurocognitive functions but without deficits in social cognition is less than 1%, while the opposite (spared neurocognitive function and impaired social cognition) is considerably higher (25%). Furthermore, a large portion of improvement of social cognition (83%) is explained by enhancement of neuropsychological performance (Vauth et al, 2004).…”
Section: Intervening Variables and Social Cognition: The Relations Tomentioning
confidence: 96%